Pengaruh Program Latihan Resistensi Pita Elastis terhadap Peningkatan Kekuatan Otot Ekstremitas Atas dan Bawah pada Lansia Sarkopenia - Mustofa, Rizal; Ismail, Rifky; Julianti, Hari Peni; Setiyana, Budi (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND : Prevention and treatment of sarcopenia are important to achieve physical health in aging, including maintaining the physical ability to live independently and carry out daily activities. AIMS :  To determine the effect of a muscle-strengthening exercise program using elastic bands for 8 weeks in order to increasing muscle strength in elderly people with sarcopenia. Arm muscles (biceps and triceps) and leg muscles (quadriceps and gastrocnemius) were measured. METHOD : An intervention study with a one-group pre- and post-test design. Subjects were taken from the elderly home by as many as five women and five men. Subjects were given strengthening exercises using elastic bands in as many as 2 sets; each set was done in as many as 10 movements, and each movement was given a rest interval of 30 seconds. The elastic band strengthening exercise program was carried out three times per week, with a period of eight weeks, so that the total training was 24 sessions. Changes in muscle strength were measured using a MicroFET2 hand-held dynamometer. Furthermore, the results of muscle measurements were tested using the paired-samples T test to determine the difference in muscle strength between before and after doing the exercise program. RESULT : Female and male subjects had an insignificant average age of 68.80 ± 5.12 years for women and 68.60 ± 5.64 years for men. The average BMI value in women and men had an ideal value of 24.38 ± 2.89 kg/m2 and 24.82 ± 5.65 kg/m2. The right limbs in the biceps, triceps, quadriceps, and gastrocnemius muscles each experienced an increase in muscle strength during the intervention, namely 2.67 kg, 2.14 kg, 1.99 kg, and 1.87 kg. Then for the left limbs, the biceps, triceps, quadriceps, and gastrocnemius muscles also experienced an increase, namely 2.96 kg, 1.42 kg, 2.28 kg, and 2.51 kg. The intervention carried out in this study can significantly increase upper limb and lower limb muscle strength (p<.05). CONCLUSION : Resistance training using elastic bands routinely for 8 weeks can increase the strength of the biceps, triceps, quadriceps, and gastrocnemius muscles. This exercise can also reduce the risk of sarcopenia and improve the quality of life for the elderly. This exercise program can be a recommendation for intervention because it is economical and easy to do independently at home.